Spatio-temporally separated cortical flows and spindle geometry establish physical asymmetry in fly neural stem cells. Issue 1 (December 2017) - Roubinet, Chantal; Tsankova, Anna; Pham, Tri; Monnard, Arnaud; Caussinus, Emmanuel; Affolter, Markus; Cabernard, Clemens
Abstract Asymmetric cell division, creating sibling cells with distinct developmental potentials, can be manifested in sibling cell size asymmetry. This form of physical asymmetry occurs in several metazoan cells, but the underlying mechanisms and function are incompletely understood. Here we useDrosophila neural stem cells to elucidate the mechanisms involved in physical asymmetry establishment. We show that Myosin relocalizes to the cleavage furrow via two distinct cortical Myosin flows: at anaphase onset, a polarity induced, basally directed Myosin flow clears Myosin from the apical cortex. Subsequently, mitotic spindle cues establish a Myosin gradient at the lateral neuroblast cortex, necessary to trigger an apically directed flow, removing Actomyosin from the basal cortex. On the basis of the data presented here, we propose that spatiotemporally controlled Myosin flows in conjunction with spindle positioning and spindle asymmetry are key determinants for correct cleavage furrow placement and cortical expansion, thereby establishing physical asymmetry. Asymmetric cell division can generate daughter cells with cell size asymmetry, but the underlying mechanisms are not clear. Here the authors show that spatiotemporally controlled Myosin flows together with spindle asymmetry and positioning control cleavage furrow position and cortical expansion to establish physical asymmetry.